Nanoemulsion Optimization of Dayak Onion (Eleutherine bulbosa (Mill) Urb.) Tuber Ethanol Extract Using Varying Concentration of VCO, Tween 80, and PEG 400 - Putri, Rizqa Akhriana; Syamsul, Eka Siswanto; Warnida, Husnul (Jurnal Kefarmasian Indonesia, 2025)
Indonesia hosts various medicinal plants, including Dayak onion (Eleutherine bulbosa (Mill.) Urb), which contains isoliquiritigenin, a flavonoid with potential anticancer activity. However, its low solubility limits bioavailability and therapeutic effectiveness. To improve drug delivery, nanoscale formulations such as nanoemulsions can enhance membrane penetration and target reach. This study aimed to optimize a nanoemulsion formulation of Dayak onion ethanol extract using the Self-Nanoemulsifying Drug Delivery System (SNEDDS) method with variations of VCO, Tween 80, and PEG 400. The nanoemulsion’s characteristics and stability were evaluated experimentally and analyzed statistically using the Independent T-Test, comparing results from Design Expert 12 and laboratory data. The optimized formulation produced a clear pink, stable nanoemulsion for one month, with a pH of 3.94 ± 0.22, transmittance of 58.45 ± 6.01%, particle size of 319.07 ± 1.05 nm, PDI of 0.44 ± 0.06, zeta potential of −31.5 ± 0.26 mV, and a creaming index of 0.